The Seasonal Assessment of Heavy Metals Pollution in the Waters of the Mediterranean and Atlantic Seas of Morocco - S. Karim; A. Aouniti; C. Belbachir (European Scientific Journal, ESJ, 2025)
Heavy metal pollution in marine environments poses a major risk to ecosystems and human health due to the persistence, bioaccumulation, and toxicity of metals. The current study aimed to analyze the seasonal patterns of cadmium (Cd), lead (Pb), zinc (Zn), iron (Fe), copper (Cu), chromium (Cr), and nickel (Ni) in seawater samples from two Moroccan coastal regions, Mediterranean Coast (Nador) and Atlantic Coast (Casablanca), during autumn and spring of the 2023-2024 season. A total of 36 water samples were collected from each coast and were analyzed using ICP-AES following the WHO and USEPA guidelines. The data showed that during both coastal regions, Cd concentrations were 0.002 mg/L to 0.020 mg/L, which is above the WHO limit of 0.003 mg/L. Pb concentrations were also higher than the WHO guideline of 0.01 mg/L and reached 0.036-0.120 mg/L, particularly in Casablanca. On the other hand, Fe and Zn concentrations of 0.010-0.255 mg/L and 0.061-0.255 mg/L, respectively, were within safe limits. Seasonal changes showed greater Cd and Pb concentrations in autumn, most likely due to industrial discharges and agricultural runoff. The study raises alarm on the high levels of Cd and Pb contamination in the Mediterranean region and the need to develop policies to properly manage wastewater, regulate industries, and conduct biomonitoring of marine species.